THE EFFECT OF DISCOVERY LEARNING MODEL TOWARD STUDENT HIGHER ORDER THINKING SKILLS IN DYNAMIC ELECTRICITY SUBJECT MATTER AT SMA RAKSANA MEDAN ACADEMIC YEAR 2014/2015 - Kristin Natalia Tondang; Sahyar . (INPAFI (Inovasi Pembelajaran Fisika), 2016)
ABSTRACT Study aimed to analyze the effect of discovery learning model toward student’s higher order thinking skill. The type of this research was quasi experimental, with experiment class used discovery learning and control class used conventional learning. The population was all of the tenth class of SMA Raksana Medan academic year 2014/1015 which consist of seven classes. Sample was taken with a simple random sampling technique. The data in higher order thinking skill was collected by essay tests. Data analyzed with t test. The result of the study showed that there was positive effect of discovery learning model toward student’s higher order thinking skill in experiment class or given by discovery model. It proved from posttest result in experiment class was higher than control class or there was significant difference of post test score, although in higher order thinking level, both of class still in less level, but student who given discovery learning had higher value than control class.   Keyword : Conventional Learning; Discovery Learning Model; Higher Order Thinking Skill